Collaboration Skills in Seventh Grade English Textbooks: An Analysis Using the Cambridge Life Competencies Framework - Tary Arshabilla; Nurkhamidah, Neni (English Language Education Department, Faculty of Teacher Training and Education, Syekh-Yusuf Islamic University (PBI FKIP UNIS), 2024)
This study aims to determine the integration of collaboration skills in the seventh grade English textbook